Environmental priorities as quantitative evaluation categories - Grodzynskyi, M. D. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
The environmental priority is considered as the evaluation category that could be evaluated quantitatively using objective information about the area and human impacts on its landscapes. The environmental priorities are of different types, namely spatial, problem-oriented, technological, geoecological, regulatory (normative), conservational. The formulas for their quantitative evaluation are presented.The article is written under the support of the Research Fund of the Hankuk University of Foreign Studies (South Korea).